2021
DOI: 10.1038/s41377-021-00682-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmissive-detected laser speckle contrast imaging for blood flow monitoring in thick tissue: from Monte Carlo simulation to experimental demonstration

Abstract: Laser speckle contrast imaging (LSCI) is a powerful tool to monitor blood flow distribution and has been widely used in studies of microcirculation, both for animal and clinical applications. Conventionally, LSCI usually works on reflective-detected mode. However, it could provide promising temporal and spatial resolution for in vivo applications only with the assistance of various tissue windows, otherwise, the overlarge superficial static speckle would extremely limit its contrast and resolution. Here, we sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Laser speckle contrast imaging (LSCI) is a wide-field, noninvasive imaging technique with high temporal and spatial resolution, that is based on the scattering properties of moving particles (e.g., red blood cells) [ 9 ]. LSCI obtains the velocity information of the scattering particles and has been successfully used for neurovascular imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Laser speckle contrast imaging (LSCI) is a wide-field, noninvasive imaging technique with high temporal and spatial resolution, that is based on the scattering properties of moving particles (e.g., red blood cells) [ 9 ]. LSCI obtains the velocity information of the scattering particles and has been successfully used for neurovascular imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Different ischemia times were used to simulate mild, moderate, and severe brain injury in mice. The laser speckle blood flow imaging was used to evaluate the changes in the cerebral blood vessels of mice before and after modeling. As displayed in Figure B, the left cerebral blood flow (CBF) density of the mice in the sham-operated group was evenly distributed, while the CBF density of the left brain of the MCAO mice was significantly lower than that in the sham-operated group. After 24 h of ischemia reperfusion, the CBF density of the left brain recovered to be comparable to the sham surgery group, however, the overall CBF density became higher than that of the sham-operated group.…”
Section: Resultsmentioning
confidence: 99%
“…With 3D volumetric transport optical diffraction tomography and synthetic aperture, Li et al from Nanjing University of Science and Technology reported a novel label-free microscopy technique, which achieves 200 nm lateral and 500 nm axial resolution, on both cell lines and C. elegans imaging 9 . By using Monte-Carlo simulation following with experimental validation, Li et al from Huazhong University of Science and Technology have demonstrated that the transmissive-detected laser speckle contrast imaging showing superior performance over reflective-detection counterparts for blood flow monitoring in thick tissue, on different samples such as tissue phantom, animal, and human hands 10 .…”
Section: Label-free Imagingmentioning
confidence: 99%